CRIMINAL LIABILITY OF NOTARY IN CRIMINAL ACT COMMITTED BY NOTARY SIGNING AGENT - Rossulliati, Dwi; Ucuk, Yoyok; Prawesthi , Wahyu (YURIS: Journal of Court and Justice, 2023)
This research aims to analyze and examine how the responsibility of a notary in the case of a notary's signing agents commits the crime of document forgery. Article 1 paragraph (1) of Notary Office Law states that a Notary is a Public Official authorized to do authentic deeds and has other authorities as referred to in this Law or based on other laws. The notaries get authority attribution from the state through the Law on Notary Positions. This authority is attached to the position of a notary. In conducting these duties and positions, a Notary is generally assisted by Notary signing agents. In this research, Normative Law is used because it tries to find the location of coherence, namely legal rules and legal norms. Notary workers are only assistants in their work, and the responsibility for authentic deeds remains to the Notary. When the Notary signing agents commit document forgery, resulting in defects in the authentic deed, it is possible that Notary must hold responsible for this. The forgery of letters can occur due to fake contents of the letter or fake authority and contents of authority in the letter. The forms of Notary Criminal Liability, if it is proven that the notary worker committed the crime of forging letters, is a crime of participation in the crime of forging letters because the Notary is considered negligent in conducting his duties and position.